Evaluation of the protective efficacy of a spatial repellent to reduce malaria incidence in children in Mali compared to placebo: study protocol for a cluster-randomized double-blinded control trial (the AEGIS program) - Van Hulle, Suzanne; Sagara, Issaka; Mbodji, Momar; Nana, Ghislain Ismael; Coulibaly, Mamadou; Dicko, Alassane; Kone, Mamady; Thera, Ismaila; Sylla, Daman; Traore, Mamadou Diango; Liu, Fang; Grieco, John P.; et al. (Current controlled trials in cardiovascular medicine, 2022)
Spatial repellents have been widely used for the prevention of mosquito bites but their efficacy in reducing mosquito-borne diseases has never been evaluated in Africa. Additionally, spatial repellents have the potential of being critical tools in the prevention of mosquito-borne diseases in contexts where typical vectors control efforts such as insecticide-treated nets (ITNs) and indoor residual spray (IRS) are inaccessible or underutilized such as among displaced populations or in emergency relief settings. To address this knowledge gap, Kolondieba District, Sikasso Region, Mali was selected as a site to estimate the impact of the Mosquito Shield™, a spatial repellent that incorporates transfluthrin on a plastic sheet, on malaria-related outcomes. Over the past decade, the Region of Sikasso, Health districts of Kadiolo, Yorosso, and Kolondieba have remained among the most afflicted, characterized by an annual parasite incidence of more than 116 cases per 1000 population [1] and a Plasmodium falciparum prevalence rate of 29.7% [2]. Cluster-randomized, placebo-controlled, double-blinded clinical trial, whereby children ≥ 6 months to < 10 years old will be enrolled and followed to determine the time to malaria infection with monthly blood samples for microscopic diagnosis. A total of 1920 subjects (HHs) will be enrolled in 60 clusters (30 spatial repellent, 30 placebo). Malaria incidence will be estimated and compared to demonstrate and quantify the protective efficacy (PE) of a spatial repellent, in reducing malaria infection. Monthly mosquito collections using CDC light traps will be conducted to determine if there are entomological correlates of spatial repellent efficacy that may be useful for the evaluation of new spatial repellents. Quarterly human landing catches (HLC) will assess the behavioral effects of the intervention. Findings will serve as an efficacy trial of spatial repellent products for sub-Saharan Africa. Findings will be submitted to the World Health Organization Vector Control Advisory Group (WHO VCAG) for assessment of whether spatial repellents have "public health value." Entomological outcomes will also be measured as proxies of malaria transmission to help develop guidelines for the evaluation of future spatial repellent products. ClinicalTrials.gov NCT04795648 . Registered on March 12, 2021.